Political Connection, Ownership Structures and Tax Aggressiveness: The Case of Indonesia - Agita Zafi Rahmasari; Agung Nur Probohudono; Doddy Setiawan (AFEBI Accounting Review, 2020)
The main purpose of this research is to examine the influences of political connection and ownership structures towards the tax aggressiveness in Indonesian companies. This research is a quantitative research and the samples consist of the companies listed in the Indonesia Stock Exchange in 2015-2016. Furthermore, the data used in this research is secondary data obtained from the companies’ financial reports and annual reports. The tax aggressiveness is measured with Book Tax Differences (BTD) proxy. The result of this research shows that political connection, government ownership, and foreign ownership give negative significant effects towards tax aggressiveness, while institutional ownership give no significant effect towards tax aggressiveness. The limitation of this research is the using of 2-year samples only that consist of companies in various sectors. In addition, the companies that are classified in a particular sector, are given different tax treatment by Directorate General of Taxes. This research can be beneficial for making taxation regulation in the future. This research is also expected to be the supporting literature for the next research for the scholars in the taxation and accounting field related to the company’ tax aggressiveness. This research extends the previous research by adding some type of ownership structure in analyzing factors that affect tax aggressiveness in Indonesia. The ownership structure consists of government ownership, foreign ownership, and institutional ownership. Furthermore, political connections in this study were analyzed from connections through boards of directors and commissioners.